The denaturalization of the pre-trial investigation in the Vallejo process - Nava Flores, Jesús Marcelo (2020)
The judicial process followed against César Vallejo is one of the most iconic cases of our legal system, as it not only resulted in the imprisonment of our universal poet but also took place when the foundations of our penal system were being reformed. In other words, the trial was an opportunity to demonstrate that our penal system evolved from an inquisitorial to an accusatorial system. Unfortunately, the opposite proved to be true: despite the change of code, the inquisitorial assumptions were unfairly applied against our universal poet with the purpose of ensuring his imprisonment during the instructive stage of the process, that is, before the relevant oral trial to determine his innocence. In this sense, this article seeks to demonstrate how the purpose of this first stage was undermined.